PER CAPITA INCOME, FEMALE LABOR FORCE PARTICIPATION, AND HUMAN DEVELOPMENT INDEX: AN ANALYSIS OF FERTILITY RATE IN INDONESIA - Rayhan Witra Pratama; Aidil Syaputra (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2026)
This study aims to analyze the effects of per capita income, female labor force participation, and the human development index on fertility rate in Indonesia during the period 2000–2024. The study employs a quantitative approach using time-series data sourced from the Central Statistics Agency (BPS), analyzed via multiple linear regression using the Ordinary Least Squares (OLS) method. The results indicate that, simultaneously, all independent variables have a significant effect on fertility rate in Indonesia. Partially, per capita income has a positive and significant effect, meaning that an increase in income tends to be followed by a rise in fertility rate. Conversely, female labor force participation has a negative effect, suggesting that increased female involvement in the workforce leads to a decline in fertility rate due to opportunity costs. Meanwhile, the human development index has a significant negative effect, indicating that improvements in the quality of education, health, and living standards drive a decline in the fertility rate. The model explains approximately 85 percent of the variation in the fertility rate, demonstrating strong explanatory power. These findings confirm that the dynamics of the fertility rate in Indonesia are influenced by the simultaneous interaction of economic, social, and human development factors.